Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XII: Notes on the Chinese Metriogryllacris Karny, 1937 - Zhang, Qianwen; Pang, Siyu; Bian, Xun (Zootaxa, 2022)
This paper reports two new species based on new material deposited in Guangxi Normal University, namely Metriogryllacris (Metriogryllacris) obscurata sp. nov. (Chinese name: 纹姬蟋螽) and M. (M.) hamata sp. nov. (Chinese name: 小钩姬蟋螽). Also, the female sex of M. (M.) bimacula Yu, Liu & Bian, 2022 and male sex of M. (M.) nigrilimbis Liu & Bian, 2021 are firstly described.